2020
DOI: 10.3346/jkms.2020.35.e268
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Community-based Noncommunicable Disease Control Program in Korea: Patients 65 Years of Age or Older

Abstract: Background In Korea, the Korean Community-based Noncommunicable Disease Prevention and Control Program (KCNPC) was implemented in 2012 for the management of patients with chronic diseases. Nineteen primary care clinics, public health centers, and education and consulting centers (ECCs) participated in the implementation of this program. This study assessed the effectiveness of this chronic disease control model by comparing mortality rate and the incidence of complications between patients partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In South Korea, urban-rural differences in obesity trends reverse following industrialization and are exacerbated by rural challenges. Despite the implementation of several nationwide health initiatives targeting chronic disease prevention and management, such as the Korean community-based Registration and Management Program for Hypertension and Diabetes, 16 the Non-communicable Diseases Prevention and Control Program, 17 and the Primary Care Project, 18 healthcare service utilization still shows significant variation with urbanicity, indicated by the National Health Insurance Service. 16 Therefore, to effectively address this urban-rural gap in obesity rates, tailored interventions for rural areas, including telehealth and web-based programs, are essential.…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, urban-rural differences in obesity trends reverse following industrialization and are exacerbated by rural challenges. Despite the implementation of several nationwide health initiatives targeting chronic disease prevention and management, such as the Korean community-based Registration and Management Program for Hypertension and Diabetes, 16 the Non-communicable Diseases Prevention and Control Program, 17 and the Primary Care Project, 18 healthcare service utilization still shows significant variation with urbanicity, indicated by the National Health Insurance Service. 16 Therefore, to effectively address this urban-rural gap in obesity rates, tailored interventions for rural areas, including telehealth and web-based programs, are essential.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the AHRs for ACSC in 2014 were 1426 per 100 000 people, and this rate has been decreasing since 2005 [ 26 ]. In Korea, national programs such as the NQAP for chronic diseases [ 20 ], the Chronic Disease Care System program [ 27 ], the Korean Community-based Noncommunicable Disease Prevention and Control program [ 28 ], and the Pilot Project for Primary Care Chronic Disease Management [ 29 ] have been implemented to encourage the public to manage chronic diseases. According to the NQAP report on chronic diseases, the medication adherence rate in 2019 was 91.9% for both hypertension and diabetes, reflecting slight increases since 2011, when the rates were 88.9% and 88.0%, respectively [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive relationship between the proportion of hospitals with good diabetes management and walking activity can be explained by the health education provided by medical personnel to diabetic patients to have a good lifestyle. Several large-scale chronic disease management programs implemented in the South Korea Program [ 8 , 9 ] reported that education and consulting improved disease management. However, since the proportion of hospitals with good diabetes management in our study did not show an association between smoking rate and obesity rate, it is possible that the proportion of hospitals with good diabetes management may proxy other characteristics at the regional level.…”
Section: Discussionmentioning
confidence: 99%
“…To improve diabetes complication management, various projects have been implemented in South Korea, including the Korean community-based Registration and Management Program for Hypertension and Diabetes [ 7 ], the Non-communicable Diseases Prevention and Control Program [ 8 ], and the Primary Care Project [ 9 ]. Health Insurance Review and Assessment (HIRA) evaluates treatment outcomes in clinics and hospitals for chronic diseases such as hypertension, diabetes, and asthma, and provides financial incentives to primary care clinics and hospitals with good outcomes.…”
Section: Introductionmentioning
confidence: 99%